Borderless Preaching by Shaykh Salar Rasoul: Integrating Pop Culture into Islamic Discourse - Ahmad Kavin Adzka (Alhadharah: Jurnal Ilmu Dakwah, 2026)
This study examines how Shaykh Salar Rasoul (SSR) (@shaykhrasoul), a Canadian imam and influential digital religious figure, integrates global pop culture into his da‘wah to create a form of “borderless preaching.” Through a digital observation analysis of his TikTok and Instagram videos, particularly those referencing popular culture such as Beyblade and Formula 1. The research explores how SSR employs pop culture as a shared global language to communicate Islamic principles in relatable and entertaining ways. Findings show that SSR's approach relies on semantic bridging, transforming widely recognized cultural symbols into moral lessons that resonate with diverse, international audiences. His humorous, personable style and cultural fluency enable his content to circulate beyond Muslim communities and become part of global digital discourse. This study situates SSR within broader frameworks of globalization, digital religion, and mediascapes, demonstrating how he exemplifies a modern model of da‘wah that adapts effectively to contemporary global cultural flows while retaining the authenticity of Islamic teachings. KEYWORDS borderless preaching; globalization; pop culture; Shaykh Salar Rasoul; social media preaching.